Interventions to bolster succes : the experiences of nontraditional students in higher education - Cooke, Amy; Cross, Penelope; Newcomb, Sara Allen (2016)
This intervention focused on nontraditional students at McDowell Technical Community College and Gardner-Webb University and the importance of bolstering their educational success. Community colleges and private institutions of higher learning enroll a significant number of nontraditional students. It is often difficult for these students to earn a credential or achieve their educational goals due to their defining characteristics. With an extensive population of nontraditional students, it is imperative that these institutions provide deliberate support services that identify, address, and reduce probable barriers these adult learners may encounter. Like other state and private agencies, educational institutions are held to a high standard. Accountability is in the forefront of every public and private institution. All colleges and universities are closely monitored and held accountable for the outcomes of their students. As a result, a portion of monetary resources may be contingent on program performance. While any reduction in funding can have a negative impact on the institution, one must not overlook the economic impact on the earning potential of nontraditional students. Through the implementation of a proactive advising model, nontraditional students at McDowell Technical Community College and Gardner-Webb University increased their ability to achieve their educational goals. The intent of the interventions was to foster deep change by capitalizing on existing human relationships formed during new student orientation, proactive advising and student mentoring. The disquisition team defined the problem, shared interventions, and analyzed the results of the collaborative improvement process.